PEMANFAATAN APLIKASI iGOGREEN UBAH SAMPAH MENJADI RUPIAH BERBASIS ANDROID DI SMK MUHAMMADIYAH 1 PALEMBANG - Rahmawati, Desi; Juliansa, Pepes Redi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to explain how to manage waste for the community to emphasize the large amount of waste in Indonesia. As for the background of this writing, Indonesia is the second largest contributor to plastic waste in the world, reaching 187.2 million tons. This is because the management of plastic waste in Indonesia is not optimal and because of the low level of awareness the public will care about the environment. Even though the government has implemented rules about the prohibition of littering, it turns out that this has not been able to overcome the problem of garbage in Indonesia, especially in the city of Palembang. The amount of waste in Palembang reaches 500 to 1000 tons per day and continues to accumulate in landfills. Therefore, to overcome this problem the author took the initiative to make a research about the use of android-based iGoGreen application that has been applied at Muhammadiyah 1 Vocational School Palembang. This practical application makes it easy for users to distribute plastic waste to iGoGreen partners for further recycling. This research is a qualitative research. The results of the utilization of this application show that the amount of plastic waste in Muhammadiyah 1 Vocational School is reduced, the level of awareness of the residents of Palembang 1 Muhammadiyah Vocational School towards environmental hygiene has increased and provided an additional income fund of an average of Rp. 58,000 for every week.